Policy Brief 2: Social norms, mental models and other behavioural drivers of petty corruption: The case of Uganda - Baez Camargo, Claudia; Stahl, Cosimo (Basel Institute on Governance Policy Briefs, 2017)
This policy brief summarises the main findings and lessons learned from research on corruption, social norms and behaviours in Uganda. The empirical evidence indicates that behavioural factors associated to social practices and collective understandings play a role in shaping Ugandan citizens’ attitudes towards petty corruption and in fuelling practices such as bribery and favouritism. On the basis of the research findings, policy recommendations are put forward aiming to contribute to the development of anti-corruption interventions that incorporate behavioural insights in their design and implementation.